Development of resolved CFD–DEM coupling model for three-phase flows with non-spherical particles. (5th March 2023) - Washino, Kimiaki; Chan, Ei L.; Tsujimoto, Taichi; Tsuji, Takuya; Tanaka, Toshitsugu
Graphical abstract: Highlights: A resolved CFD–DEM coupling model for gas–liquid-solid three-phase flows with non-spherical particles is developed. Particle shape is implicitly captured by a superquadric function. Hydrodynamic and capillary interaction forces are directly obtained from simulation. Particle shape can have a large impact on the fluid-particle interactions and resultant particle movement. Abstract: In this work, a resolved CFD–DEM coupling model for gas–liquid-solid three-phase flows with non-spherical particles is developed where the shape of the particle is implicitly captured by a superquadric function. Both gas–liquid and fluid–solid interfaces are smoothly represented with a specified thickness so that the interface thicknesses and CFD cell size are independent of each other. Several sensitivity studies are carried out and criteria for mesh- and thickness-independent results are proposed. It is confirmed that the proposed model can properly predict the hydrodynamic and capillary forces acting on particles with a wide range of shapes and contact angles. Finally, the model proposed is applied to perform several virtual experiments of typical chemical engineering processes: a liquid–solid fluidised bed and bubbly flow with various particle shapes. It is found that particle shape can have a significant impact on the fluid-particle interactions and resultant particle movement, leading to segregation and preferential alignment.